Polymorphism in DNA repair gene BRCA1 associated with clinical mastitis and production traits in indigenous dairy cattle. (December 2020) - Magotra, Ankit; Gupta, I.D.; Ahmad, Tavsief; Alex, Rani
Abstract: The present study was conducted on Karan Fries cows to identify SNPs in breast cancer 1 (BRCA1) gene and their association with inflammation of mammary gland and production traits. Chi square analysis showed significant association of both SNPs i.e. G43737229T ( P < 0.01) and G43761121A ( P < 0.05) with incidence of clinical mastitis. Logistic modeling showed that GG genotype cows of G43737229T SNP was less susceptible to mastitis in comparison to TT genotype cows as the odds ratio of TT against GG for the non-incidence of mastitis was less i.e. 0.23. Whereas, cows with genotype AA of G43761121A SNP were less prone to clinical mastitis in comparison to GG genotype cows. G-T haplotype and GGTT combined genotype exhibited maximum mastitis incidences. Least squares analysis revealed significant association of G43737229T SNP with total milk yield ( P < 0.01), 305 days milk yield (P < 0.01) and lactation length ( P < 0.05). The TT and GT genotyped Karan Fries cows were associated with higher milk yields during first and second lactation, as well as with first lactation length. These observations on SNPs, genotypes and combined genotypes of BRCA1 gene and their differential association with the incidence of mastitis and production traits can be utilized as an aid to selection for simultaneous improvement of both antagonistic traits. Highlights: Genotype GG of G43737229T SNP and AA of G43761121A SNP of BRCA1 gene was less susceptible to clinical mastitis. The TT and GT genotypes (G43737229T) in Karan Fries cows were associated with higher milk yields (P < 0.01) and first lactation length (P < 0.05). G-T haplotype and GGTT combined genotype found to be more prone to mastitis incidences.